POLITICAL AND ECONOMIC INTERESTS OF THE CENTRAL ASIAN STATES - Takhmina MAMADALIEVA (Scholar Express Journals, 2022)
The article contains an analysis of the political and economic interests of the Central Asian states, as well as relations between the EU and Central Asia. The main attention paid to the new EU strategy in Central Asia as an important mechanism for stabilizing the region and its development.
Keywords: EU; Central Asian; development; new strategy